Random walks on stochastic hyperbolic half planar triangulations. Issue 2 (20th June 2016) - Angel, Omer; Nachmias, Asaf; Ray, Gourab
Abstract: We study the simple random walk on stochastic hyperbolic half planar triangulations constructed in (Angel and Ray, Ann Probab, in press). We show that almost surely the walker escapes the boundary of the map in positive speed and that the return probability to the starting point after n steps scales like exp ( − c n 1 / 3 ) © 2016 Wiley Periodicals, Inc. Random Struct. Alg., 49, 213–234, 2016